The Transmission of Arabic Culture at Darullughah Wadda’wah Islamic Boarding School (DALWA) in Bangil, Pasuruan - Wigianiska, Trevina; Imam Wicaksono (PT. Intelek Cendikiawan Nusantara, 2025)
This study examines the transmission of Arab culture at Pesantren Darullughah Wadda’wah (DALWA) in Bangil, Pasuruan, which serves as a key center for the integration of Hadrami traditions into the Indonesian pesantren system. The research employs a library research method, focusing on cultural transmission theory to explore how Arab norms and practices are internalized within the pesantren’s educational, social, and spiritual activities. The findings reveal that DALWA implements Arab cultural elements through daily routines, such as attire, communal dining, and halaqah teaching methods, alongside spiritual practices like Ratib Haddad recitations. Additionally, the pesantren emphasizes Arabic language instruction (fusha and Hadrami lahjah) to ensure both religious literacy and practical communication skills. Leadership by Habaib and connections to Middle Eastern institutions strengthen the transmission process, showcasing a balance between preserving tradition and adapting to modern challenges. This study highlights DALWA’s role as a mediator of Arab culture, providing a model for dynamic cultural integration in Islamic education.